Parallel Algorithms for Using Lagrangian Markers in Immersed Boundary Method with Adaptive Mesh Refinement in FLASH - Mohapatra, Prateeti; Dubey, Anshu; Daley, Christopher; Vanella, Marcos; Balaras, Elias (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2013)
Computational fluid dynamics (CFD) are at the forefront of computational mechanics in requiring large-scale computational resources associated with high performance computing (HPC). Many flows of practical interest also include moving and deforming boundaries. High fidelity computations of fluid-structure interactions (FSI) are amongst the most challenging problems in computational mechanics. Additionally, many FSI applications have different resolution requirements in different parts of the domain and therefore requirement adaptive mesh refinement (AMR) for computational efficiency. FLASH is a well established AMR code with an existing Lagrangian framework which could be augmented and exploited to implement an immersed boundary method for simulating fluid-structure interactions atop an existing infrastructure. This paper describes the augmentations to the Lagrangian framework, and the new parallel algorithms added to the FLASH infrastructure that enabled the implementation of immersed boundary method in FLASH. The paper also presents scaling behavior and performance analysis of the implementations.